ANALISIS DAMPAK MIKRO KEPARIWISATAAN DI PROVINSI NUSA TENGGARA TIMUR - Frits O Fanggidae (Journal of Management Small and Medium Enterprises (SMEs), 2015)
NTT tourism showed good development in terms of the increase of tourists arrival and tourisminfrastructure such as hotels, restaurants, and other tourism services. In line with thesedevelopments, the analysis of the impact of micro showed that, the effect of tourist spending to theimprovement of people's income is large enough, but the backward linkages with other economicsectors (upstream) is not adequate, resulting in suppliers (upstream) benefit is relatively smallcompared to the actors in the sector downstream. In terms of employment, a positive multipliergreater than one, but not optimal. This suggests that other economic sectors has not responded toquickly increase demand of the tourism sector. All this indicates that institutional improvement tocreate a strong backward linkages need to be done, as well as efforts to increase the capacity of thetourism-related sectors of the economy need to be done. To use the recommended industry clusterapproach to strengthen backward linkages and capacity of tourism related sector of the economy. Keywords : Tourism, Keynesian Local Income Multiplier, Ratio Income Multiplier